Uptake of long-acting reversible contraceptives in north central Nigeria: a five-year review - Jumbo, Caroline H.; Muhammad, Rafat B.; Adewole, Nathaniel D.; Isah, Dennis A.; Offiong, Richard A.; Abdullahi, Habiba I. (International Journal of Research in Medical Sciences, 2021)
Background: Long-acting reversible contraceptives (LARC) are methods used in the prevention of pregnancy that are long lasting. They are effective and efficacious methods of contraception and return to fertility after removal is prompt. Objectives was to determine the uptake of long-acting reversible contraception and assess the characteristics of acceptors of these methods in the area. Methods: This was a retrospective study of clients’ who visited the family planning unit of the University of Abuja teaching hospital over a 5-year period, from 01 January 2015 to 31 December 2019. Information on socio-demographic characteristics and specific methods selected were extracted from their records and represented on simple tables, graphs, and charts. Results: A total of one thousand eight hundred and ninety-one (1,891) clients accepted available methods of contraceptives during the five-year study period. One thousand seven hundred and twenty-four (1,724) accepted LARC (91.1%) while only one hundred and sixty-seven (167) accepted non-LARC (8.9%). Majority 946 (54.9%) of the clients that accepted LARC were aged between 30-39 years and clients less than 20 years were 22 (1.3%). Clients with parity 3 and above were 1162 (67.7%), and majority of LARC acceptors wanted more children 1145 (66.4%). Amongst the LARC acceptors, most of the clients opted for subdermal implant either Jadelle or Implanon 940(49.7%). Three hundred and ninety-eight (23.1%) discontinued a form of LARC during the study period while 1127 (65.4%) continued with one form of LARC or another. Conclusions: The uptake of LARC in this region is very high. Teenagers and low parity rarely attended the family planning clinic.